2017
DOI: 10.3390/su9030468
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Certified Artisan Cheese Production through Systemic Analysis—Serra da Estrela PDO

Abstract: This research was aimed at improving the overall efficiency of the PDO (Protected Designation of Origin) Serra da Estrela cheese production process, a traditional food product with cultural significance. Mapping of the manufacturing and distribution processes was developed from systemic analysis using ethnographic techniques. Critical points were identified, leading to design work. Ergonomic risks in cheese making were detected during the process of chips cutting, fostering the emergence of musculoskeletal dis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…Following the set guidelines enables business actors in the SSC supply chain to label their cheese with the PDO certificate and promote it as such in the market [38]. All investigated companies involved in the production are characterized by being family-owned micro-enterprises, i.e., small businesses employing 10 people or fewer (family-style management and traditional organization, production depends on the amount of milk collected, control is unsupported by information systems, orders are sent from points of sale via telephone, and most product goes to stock [17]). In terms of marketing practices, Siu and Kirby [64] suggested that small firms usually do not have formal marketing policies and that they are unaware of their strategic decisions; therefore, they proposed analyzing stories about owner-managers and their companies to identify strategic marketing decisions in their firms.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Following the set guidelines enables business actors in the SSC supply chain to label their cheese with the PDO certificate and promote it as such in the market [38]. All investigated companies involved in the production are characterized by being family-owned micro-enterprises, i.e., small businesses employing 10 people or fewer (family-style management and traditional organization, production depends on the amount of milk collected, control is unsupported by information systems, orders are sent from points of sale via telephone, and most product goes to stock [17]). In terms of marketing practices, Siu and Kirby [64] suggested that small firms usually do not have formal marketing policies and that they are unaware of their strategic decisions; therefore, they proposed analyzing stories about owner-managers and their companies to identify strategic marketing decisions in their firms.…”
Section: Resultsmentioning
confidence: 99%
“…Observation fieldwork showed that SSC is not available in the other two nationally present retailing chains-Dis and Idea. The same challenges appear to be shared by less recognizable PDO cheeses in Europe [17], but also some well-known DOLs [18]. The prices at both distribution levels-wholesalers and retailers-are depicted in Table 2.…”
Section: Type Of Organizationmentioning
confidence: 89%
See 2 more Smart Citations
“…Most of these cheeses have a protected designation of origin that contributes to their valorization and adds market value. Although these cheeses still represent market niches, they are an important source of income for local communities and have a high impact on the preservation of specific regional breeds of sheep and goat [2]. The use of plant APs as rennet in cheese manufacturing is mainly driven by the shortage in animal rennet, which is extracted from the stomach of young calves.…”
Section: Introductionmentioning
confidence: 99%